Association of platelet count and plateletcrit with nerve conduction function and peripheral neuropathy in patients with type 2 diabetes mellitus. Issue 10 (23rd March 2021) - Qian, Yuqin; Zeng, Yaying; Lin, Qingxia; Huang, Huanjie; Zhang, Wanli; Yu, Huan; Deng, Binbin
Abstract: Aims/Introduction: Diabetes has been considered as a 'pro‐thrombotic state' with enhanced platelet reactivity. Abnormality in platelet aggregation has been found in patients with its most common chronic complication – diabetic peripheral neuropathy (DPN). The purpose of this study was to investigate the potential association of platelet indices with nerve conduction function and the presence of DPN in Chinese patients with type 2 diabetes mellitus. Materials and Methods: This study involved a total of 211 inpatients with type 2 diabetes mellitus and 55 healthy individuals for whom nerve conduction studies were carried out. DPN was diagnosed according to the American Diabetes Association recommendation. Clinical data were retrospectively collected. Results: Patients with diabetes in whom neuropathy developed had lower levels of platelet count (PLT) and plateletcrit (PCT) than healthy controls ( P  < 0.05). Statistically significant associations of low PLT and PCT levels with the reduction of summed amplitude/velocity Z‐score, and the prolongation of F‐wave minimum latency in nerve conduction studies were found. Furthermore, after multivariate adjustment, logistic regression analysis showed that low levels of PLT (odds ratio 2.268, 95% confidence interval 1.072–4.797; P  < 0.05; PLT <226 vs PLT ≥226) and PCT (odds ratio 2.050, 95% confidence interval 1.001–4.201; P  < 0.05; PCT <0.222 vs PCT ≥0.222) in type 2 diabetes mellitus patients were risk factors for the presence of DPN. Conclusions: Lower PLT and PCT levels are closely associated with poorer peripheral nerve conduction functions and the presence of neuropathy in patients with type 2 diabetes mellitus, which suggests that PLT and PCT might be potential biomarkers for showing DPN. Abstract : Diabetes has been considered as a 'pro‐thrombotic state' with enhanced platelet reactivity. In this study, we found that lower platelet count and plateletcrit levels are closely associated with poorer peripheral nerve conduction functions and the presence of neuropathy in patients with type 2 diabetes mellitus. Platelet count and plateletcrit might be potential biomarkers of showing diabetic peripheral neuropathy.